Correlation between social support and the achievement of the development of self-concept to deaf children 7 – 12 years - Siti Nurmalasari; Tantut Susanto; Kholid Rosyidi Muhammad Nur (Journal of Community Empowerment for Health, 2020)
Children with deaf have a disability in language and communication because they cannot hear and understand their environment, so that is not uncommon for people around them to assume that children with deaf cannot live in the social environment. This matter shows the community to deaf children where it can affect children's self-concept with the deaf. This research aims to analyze the correlations between social support and self-concept in children with the deaf. A cross-sectional study was used to examine 51 children with deaf 7 – 12 years selected with a convenience sampling method. The questionnaire consisted of identity data used to measure participant characteristics. Social Support Questionnaire for children (SSQC) was used to measure social support and the Self-Description Questionnaire to measure self-concept. The Chi-Square test is used to answer the objectives of this study. From 51 respondents, 44 (86.3%) deaf children received good social support, with the most social support obtained from 36 friends (70.6%) and siblings 36 (70.6%). Of the five components of social support, only social support from friends and siblings most resulted in low-deaf children's self-concept. There was a relationship between social support and the self-concept of deaf children (Z = 1.833; p-value = 0.034). Support from various sources is needed for deaf children to develop self-concept in their social life. Therefore, the child's social environment needs to provide adequate social support for developing an excellent deaf child's self-concept.